1993
DOI: 10.1080/11250009309355812
|View full text |Cite
|
Sign up to set email alerts
|

Duration of the rehabilitation period and familiarity with the prey affect the predatory behaviour of captive wild kestrels (Falco tinnunculus)

Abstract: A sample of 24 wild kestrels (Falco tinnunculus) was tested in captive conditions in order to study their predatory behaviour after a rehabilitation period from injuries. The birds, divided into two groups according to duration of captivity, were tested on three consecutive days with three types of prey: a live mouse, a dead mouse, and a chicken carcass. The results showed a significant interaction between groups and prey with regard to the movements on the perch after the prey's appearance and the exploratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…likely inducing suffocation, similarly to what is suggested in other raptor species such as the kestrel {Falco tinnunculus) and the buzzard (Buteo buteo) (Csermely et al, 1989(Csermely et al, , 1991Csermely, 1993). Moreover, the barn owls certainly become progressively used in some way to the environmental conditions during the tests, as shown by the continuous reduction of prédation latency and disappearance of the conflict patterns that were recorded mainly in the early tests.…”
Section: Discussionsupporting
confidence: 61%
“…likely inducing suffocation, similarly to what is suggested in other raptor species such as the kestrel {Falco tinnunculus) and the buzzard (Buteo buteo) (Csermely et al, 1989(Csermely et al, , 1991Csermely, 1993). Moreover, the barn owls certainly become progressively used in some way to the environmental conditions during the tests, as shown by the continuous reduction of prédation latency and disappearance of the conflict patterns that were recorded mainly in the early tests.…”
Section: Discussionsupporting
confidence: 61%
“…Previous observations (Csermely 1993) using similar tests did not find any effect of prolonged captivity on the latency to attack a mouse. In contrast, this study ascertained an effect limited to that behaviour pattern, i.e.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly to previous observations (Csermely et al 1989), no differences in behaviour between sexes were recorded for the behaviour patterns considered, mainly latency to attack, latency to ingest and frequency of beak strikes (U-test, P>0.1). Before the attack, we recorded a very few conflict behaviour patterns, such as movements on the perch and preening activity (Csermely et al 1989;Csermely 1993), as well as exploratory flights in the pen (Table 1 ). In most tests (28 of 36), regardless of prey type, predation occurred within the first 5 min after prey appearance, while in five tests predation occurred between 5 and 8 min and in the remaining three tests it occurred after 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…There are studies such as Csermely 2 and Mason 9 that, despite risks, have shown that birds of prey can be rehabilitated reasonably well despite long periods of captivity suggests that birds can be rehabilitated after long recoveries. However, limited work can be found that assesses their welfare and stress during their time in captivity.…”
Section: Analysis Of Species-based Categorization Of Cases Inmentioning
confidence: 99%